Operative hysteroscopy versus ultrasound-guided electric vacuum aspiration for removal of retained products of conception: A prospective cohort study - Liselot P. Wagenaar; Hubertus A. van Vliet; Celine M. Radder; Louisette W. Peters; Steven Weyers; Benedictus C. Schoot; Tjalina W. Hamerlynck (Elsevier, 2023)
Objectives: To compare intrauterine adhesion (IUA) formation after hysteroscopic removal (HR) of retained products of conception (RPOC) with IUA formation after ultrasound-guided electric vacuum aspiration (EVA) and externally validate the outcomes of an RCT. Study design: This prospective cohort study was conducted from April 2015 until June 2022 in 2 Dutch teaching hospitals and one Belgian university hospital. Women opting for EVA underwent the procedure as soon as possible. In the HR group, the therapeutic hysteroscopy was performed at least eight weeks after the end of pregnancy. Postoperatively, an office second-look hysteroscopy was offered to all patients. Women were included if they had been diagnosed with RPOC ranging from 1 to 4 cm on ultrasound and did not want to participate in the RCT. EVA was performed using a Karman cannula. Operative hysteroscopy consisted either of hysteroscopic morcellation with the TruClear™ System or the Intrauterine BIGATTI Shaver or cold loop resection with a bipolar resectoscope. Results: Of 178 included women, 124 were treated with HR and 28 with EVA. Outcomes of HR and EVA did not differ significantly in terms of complications (5.6 % vs 3.6 %; p = 1.00). Second-look hysteroscopy showed IUAs in 14 of 91 women (15.4 %) after HR and in 1 of 16 (6.3 %) after EVA (p = .461). Completeness of removal was significantly higher (90.1 %) after HR than after EVA (68.8 %) (p = .035). Additional operative hysteroscopy was required in 14.3 % of the HR group versus 37.5 % in the EVA group (p = .036). Conclusion: In our cohort study, no significant differences in IUAs or complications were found. RPOC removal with HR was more often complete than removal with EVA, and additional therapeutic hysteroscopy was less frequently required after HR. These findings need to be correlated with those of RCTs. Clinical trial registration: The study was registered in de Dutch Trial Register (NTR4923). Date of registration 23-11-2014. Date of first enrollment 01-01-2015. https://trialsearch.who.int/Trial2.aspx?TrialID=NTR4923